2020
DOI: 10.1002/app.49425
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect between CuCr2O4 nanoparticles and plasticizer on mechanical properties of EP/PU/CuCr2O4 nanocomposites: Experimental approach and molecular dynamics simulation

Abstract: In this research, copper chromite (CuCr2O4) nanoparticles (NPs) were synthesized by the sol–gel auto‐combustion method. The effects of CuCr2O4 NPs and polyurethane (PU) on the tensile strength of the epoxy (EP) resin were studied by considering different weight percentages (wt%). The response surface methodology (RSM) coupled with central composite design (CCD) (RSM/CCD) methods were also used to optimize the Young's modulus, yield strength, and ultimate tensile strength of the EP/PU/CuCr2O4 nanocomposites. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…The shear modulus of the nanocomposite with 25% volume of nano-silica loading reaches a value (9.0 GPa) that is 10 times higher than the value of the dry unfilled P-HEMA (0.9 GPa). These significant increases in the shear moduli compared to the values expected applying the ordinary Halpin-Tsai equations approach [ 25 ] have been attributed to the hybrid nature of the resulting nanocomposites that is stiffened at segmental level by the entangled polymer structure interpenetrating the nano-silica inorganic network [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The shear modulus of the nanocomposite with 25% volume of nano-silica loading reaches a value (9.0 GPa) that is 10 times higher than the value of the dry unfilled P-HEMA (0.9 GPa). These significant increases in the shear moduli compared to the values expected applying the ordinary Halpin-Tsai equations approach [ 25 ] have been attributed to the hybrid nature of the resulting nanocomposites that is stiffened at segmental level by the entangled polymer structure interpenetrating the nano-silica inorganic network [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding toughening mechanisms are those described previously [ 172 , 173 ]. In the work undertaken by Sarafrazi et al [ 183 ], thermoplastic polyester urethane (PU) was used to toughen a DGEBA epoxy resin containing copper chromite CuCr2O4 nanoparticles, castor oil (ECO) and montmorillonite (Cloisite 30B). A diminution in the tensile strength and rigidity was reported for the DGEBA/ECO system as a result of the decrease in the crosslinking density.…”
Section: Hybrid Epoxy Nanocompositesmentioning
confidence: 99%
“…Incorporation of TiO2/SiO2 in epoxy resin improves the elongation, yield strength, ultimate strength, and elastic modulus to 29.3, 17.72, 17.43, and 4.34%, respectively [13]. Also, NiMn2O4 and CuCr2O4 nanoparticles added to epoxy resin at the optimum percentage weight increased the yield and Young's modulus of NiMn2O4/EP/PU and CuCr2O4/EP/PU nanocomposites [14,15]. In addition, it has been reported that the nanocomposite Ag/CuO/Polyethylene Glycol in epoxy resin matrix has higher elongation [16].…”
Section: Introductionmentioning
confidence: 96%